2014
DOI: 10.1111/1475-6773.12215
|View full text |Cite
|
Sign up to set email alerts
|

Which Components of Medical Homes Reduce the Time Burden on Families of Children with Special Health Care Needs?

Abstract: Objectives. To examine which components of medical homes affect time families spend arranging/coordinating health care for their children with special health care needs (CSHCNs) and providing health care at home. Data Sources. [2009][2010] National Survey of Children with Special Health Care Needs (NS-CSHCN), a population-based survey of 40,242 CSHCNs. Study Design. NS-CSHCN is a cross-sectional, observational study. We used generalized ordered logistic regression, testing for nonproportional odds in the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…Families that lacked enabling factors for healthcare utilization had higher odds of family time burden, suggesting that access to health services is an important mechanism for reducing the time family members must spend on tasks related to their child's healthcare. Consistent with previous research (Kuo et al, 2011a;McManus et al, 2011;Miller et al, 2015;Turchi et al, 2009), we found that, even after accounting for child's health, families with public health insurance (alone or in combination with private insurance), and those without a medical home, had high odds of time burden for both arranging/coordinating and providing health care for the child at home. Past research shows that key components of the medical home for reducing time burden include family-centered care, care coordination, and obtaining needed referrals (Miller et al, 2015).…”
Section: Implications Of Research Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Families that lacked enabling factors for healthcare utilization had higher odds of family time burden, suggesting that access to health services is an important mechanism for reducing the time family members must spend on tasks related to their child's healthcare. Consistent with previous research (Kuo et al, 2011a;McManus et al, 2011;Miller et al, 2015;Turchi et al, 2009), we found that, even after accounting for child's health, families with public health insurance (alone or in combination with private insurance), and those without a medical home, had high odds of time burden for both arranging/coordinating and providing health care for the child at home. Past research shows that key components of the medical home for reducing time burden include family-centered care, care coordination, and obtaining needed referrals (Miller et al, 2015).…”
Section: Implications Of Research Findingssupporting
confidence: 89%
“…Consistent with previous research (Kuo et al, 2011a;McManus et al, 2011;Miller et al, 2015;Turchi et al, 2009), we found that, even after accounting for child's health, families with public health insurance (alone or in combination with private insurance), and those without a medical home, had high odds of time burden for both arranging/coordinating and providing health care for the child at home. Past research shows that key components of the medical home for reducing time burden include family-centered care, care coordination, and obtaining needed referrals (Miller et al, 2015). Future studies should evaluate the extent to which insurance and medical homes improve access to home health care, respite care, or other services that could alleviate time burdens on family members.…”
Section: Implications Of Research Findingssupporting
confidence: 89%
“…With respect to levels of evidence captured, studies were predominantly quasi-experimental or non-experimental, with small to medium sample sizes noted; with the exception of national level surveys with vast numbers of CSHCN families Children with medical complexity: a scoping review 329 (Arauz Boudreau et al 2012;Drummond et al 2012;Miller et al 2015;Okumura et al 2009). Findings regarding impacts of care coordination models and peer support were derived from a mix of designs, with telemedicine studies exclusively quasi-experimental.…”
Section: Discussionmentioning
confidence: 99%
“…Key aspects of medical homes (i.e. familycentred care, shared care plans, timely referrals, care coordination activities and centralized information) were associated with better family functioning through greater access to needed resources and streamlined services, thereby reducing time and financial burdens, affording fewer childcare issues and minimizing work loss (Arauz Boudreau et al 2012;Cohen et al 2012;Drummond et al 2012;Kingsnorth et al 2015;Miller et al 2015;Okumura et al 2009). Care coordinators in particular were identified as essential components in reducing overarching strain and depression scores and/or increasing caregiver satisfaction and service access (Adams et al 2013;Cady et al 2014;Carter et al 2007;Farmer et al 2005;Farmer et al 2011;Hamilton et al 2013;Kelly et al 2008;Kuo et al 2013;Lawson et al 2011;Palfrey et al 2004;Quigley et al 2014;Robson & Beattie 2004;Taylor et al 2013;Wood et al 2009a).…”
Section: Care Coordination Models (N = 23)mentioning
confidence: 99%
“…Can we boil all those guidelines down to a simple formula for primary care physicians? There have been many attempts to do this; one states that there are "five components of medical homes: usual source of care; personal doctor or nurse; family-centered care; coordinated care; and obtaining needed referrals" [8].…”
mentioning
confidence: 99%